Comparative Analysis of Proverbs in "Devonu Lug`Otit Turk" and Currently Available - Okhunjonovna, Bobojonova Dilnoza (Journal of Higher Education and Academic Advancement, 2024)
One of the main literary and linguistic monuments of the Karakhanid period is Mahmud Kashgari's encyclopedic work "Devonu lug`atit turk". This work is a valuable source that provides full information about the phonetics, lexicon, grammar, and dialectal features of the Turkic languages at that time. At the same time, it is a great artistic work that reflects examples of folk oral creativity of Turkic peoples.